A Morphological Analysis of Martin Luther King Jr’s “I HAVE A DREAM” Speech: a Compositional Semantic Perspective - DATONDJI, COCOU ANDRÉ (My University, 2023)
This research work has investigated the importance of linguistic morphology in the construction of new lexemes and grammatically conditioned words on the first hand and the way both derivational and inflectional morphemes function to carry and impart compositional meaning in text on the other. Premised on the objective of raising more awareness on the significance of morphological research, this paper has applied both the quantitative and qualitative analysis methods to the historic speech ―I Have a Dream‖ by the African American civil rights figurehead Martin Luther King Jr. The scientific roadmap thus carved has led its process through the identification, labelling and numbering of the distinctive derivational (50 /40%) and inflectional (75 / 60%) morphemes. A furthering of the quantitative input has displayed an outstanding use of nominalisations with nouns derived from adjectives 17 [13.6%] and from verbs 12 [9.6%] with bound morphemes such as ―ity‖, ―ice‖, ―ation‖, ―tion‖, ―or‖, and ―dom‖. On the inflectional part, the prevailing use of regular and irregular plural number imparting morphemes (47 / 37.6%) together with tense inflections (16 / 12.8%) pair up to confirm, in a qualitative analytical approach, the ideological perspective of the speaker to include the largest anonymous members of the African American community as the intended beneficiaries of his unquenchable soft but vibrant battle for freedom. The use of tense indicating morphemes has revealed the presence of a threefold tense progression from the past tense (simple past and past perfect) to the simple present and then to the future. The crosscheck of the semantics of such morphemic operations has uncovered the perspective of Martin Luther King Jr for the logical representation of the sufferings of the Black community and liberation struggles in the past, the need to keep the battle going in the present time with the conviction of brighter days in the future.
Keywords: linguistic morphology; inflection and derivations; morphological analysis; semantics.